2019
DOI: 10.5114/aoms.2019.82672
|View full text |Cite
|
Sign up to set email alerts
|

How much insulin resistance in polycystic ovary syndrome? Comparison of HOMA-IR and insulin resistance (Belfiore) index models

Abstract: Introduction Polycystic ovary syndrome (PCOS), the commonest endocrinopathy of women in reproductive age, is often accompanied by insulin resistance (IR), hirsutism and/or fertility problems. The aim of the study was to assess the prevalence of IR in women diagnosed with PCOS. Material and methods The study involved 137 women diagnosed with PCOS, according to the Rotterdam consensus criteria (2003). Insulin resistance was assessed according to the HOMA-IR method and ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 32 publications
3
17
0
1
Order By: Relevance
“…Recent research has confirmed that vitamin D 3 supplementation has a beneficial effect on HOMA-IR and dyslipidemia [59]. Furthermore, in one of the latest studies comparing the HOMA-IR method and insulin resistance (Belfiore) index, it was concluded that insulin resistance (Belfiore) index diagnosed more cases of insulin resistance in women with PCOS compared to HOMA-IR [60]).…”
Section: Discussionmentioning
confidence: 96%
“…Recent research has confirmed that vitamin D 3 supplementation has a beneficial effect on HOMA-IR and dyslipidemia [59]. Furthermore, in one of the latest studies comparing the HOMA-IR method and insulin resistance (Belfiore) index, it was concluded that insulin resistance (Belfiore) index diagnosed more cases of insulin resistance in women with PCOS compared to HOMA-IR [60]).…”
Section: Discussionmentioning
confidence: 96%
“…IR plays a key role in the pathophysiology of PCOS and is associated with ovulatory dysfunction and hyperandrogenism. Some mechanisms of IR in women with PCOS are connected to an excessive activity of 17 α-hydroxylase, which regulates the conversion of 17-hydroxyprogesterone into androstenedione, excessive stimulation of IGF-I receptors, and diminished synthesis of insulin-like growth factor binding protein 1 (IGF-BP1) [52].…”
Section: Discussionmentioning
confidence: 99%
“…Polycystic ovary syndrome is characterized by hyperandrogenemia and hyperinsulinemia [2]. Although insulin resistance and hyperinsulinemia are not the diagnostic criteria of PCOS, about 75% of PCOS women have the endocrine characteristics of insulin resistance [3].…”
Section: Introductionmentioning
confidence: 99%